Modelling the dispersion of airborne pollutants in the Pretoria urban area - Zib, Pavel (My University, 2014)
The theory and methodology of urban air pollution dispersion models are reviewed to provide the background for a critical approach to modelling atmospheric pollution in South African conditions. It is shown that there is no evidence to suggest the existence of a universally applicable modelling technique. Three models of various degrees of complexity, the Gaussian plume model for multiple sources, the ATDL-grid model and the Gifford-Hanna simple model, are applied to predict long-term concentrations of atmospheric sulphur dioxide in the Pretoria urban area and evaluated against observations. Whereas the ATDL-grid model does not adequately simulate air pollution levels during the main pollution season in Pretoria, more realistic results are obtained by the Gaussian plume model for multiple sources and the Gifferd-Hanna simple model. The refinements introduced into the two models to further improve their performance are presented. A closer association between predicted and observed SO2 concentrations is consistently obtained when an increasing number of wind and stability observations are used in the Gaussian plume model for multiple sources to simulate spatial variations in the dispersion conditions over Pretoria. The Gifford-Hanna simple model is refined by including estimates of hourly, monthly and seasonal air pollution concentrations. An objective weighting scheme is used in conjunction with experimental evidence to determine variations of the stability factor in the model. The methodology of future applications is discussed and it is shown that the refined Gifford-Hanna simple model provides a fast and inexpensive basis for predicting concentration levels of spheric pollutants from multiple sources with a degree of success comparable to the performance of the Gaussian plume model.